COUNTERING XENOPHOBIA AND RACISM THROUGH SHORT STORIES FOR HISTORY STUDENTS - Novita Dewi (International Journal of Humanity Studies (IJHS), 2021)
Short stories provide suitable reading materials to enrich the study of American History. Using literary works can help foster transformative history teaching, especially when discussing the violent past to construct a better future. This study aims at examining two American short stories that deal with racism and prejudice. Used as primary data are “Désirée’s Baby” (1893) which tells about racial intolerance in a pre-Civil War plantation society; and “Shame” (1964), a story about intolerance experienced by a Black schoolboy. Critical reading method is applied by making contextualization with different American historical periods. The results show that (1) themes of xenophobia, racism, and intolerance are evident in these short stories; (2) authorial backgrounds help explain their dealing with the history of racism shown in their works; and (3) stories of inter-racial relations make good reading supplements for teaching American History. In conclusion, literature is history which is beautifully condensed that can help raise students’ awareness about the evil pasts and to grow a historical empathy in facing current realities in order to build a more just, civil, and compassionate society in the future.